Long-Term Assets Exercises III - eBooks and textbooks from bookboon.com - Walther, Larry M. (bookboon.com, 2016)
This exercise book is the last of three exercise books that correspond directly with the Long-Term Assets textbook. The exercises relate specifically to Part 3 of the Long-Term Assets textbook. Exercises focus on advanced property, plant, and equipment topics, natural resources, and intangible assets.